Knowledge construction process in open learning system among technical and vocational education and training (TVET) practitioners - Suhaizal, Hashim; Mohd Hishamuddin, Abdul Rahman; Eh Phon, Danakorn Nincarean; Nurul Farhana, Jumaat; Utami, Pipit (Penerbit UTHM, 2019)
Assessment is a method to determine the level of learning and the process of documenting knowledge, attitudes, skills and beliefs. Through this literacy assessment, instructor will have an opportunity to apply relevant strategies and procedures that we re considered relevant during their teaching and learning process. However, most of us were familiar with Information and Communication Technology (ICT) based modes of delivery but less familiar with the needs and challenges face in Technical and Vocational Education and Training (TVET) sector. Thus, this study was conducted to investigate whether the process of knowledge construction in an open learning system can assist TVET practitioners in performing tasks that needed to be completed as an important element in assessment in one of their class subject. Computer Supported Collaborative Learning (CSCL) is based on the pedagogical process of observation where these TVET practitioners will learn progressively through active group interaction. The study was conducted on 61 TVET practitioners and two instructors from two classes that were taught using an open learning system environment through Moodle. This study used a quantitative design approach and supported by quantitative and qualitative data. The results of this study indicated that the process of knowledge construction in this open learning system has helped TVET practitioners to perform well in tasks that needed to be completed for their subject and also encouraged them to build a meaningful knowledge in a constant process. TVET practitioners need to explore more information and knowledge in order to justify most of their answers.